Corticofugal VIP Gabaergic Projection Neurons in the Mouse Auditory and Motor Cortex - Bertero, Alice; Garcia, Charles; Apicella, Alfonso junior (Frontiers in Neural Circuits, 2021)
Anatomical and physiological studies have described the cortex as a six-layer structure that receives, elaborates, and sends out information exclusively as excitatory output to cortical and subcortical regions. This concept has increasingly been challenged by several anatomical and functional studies that showed that direct inhibitory cortical outputs are also a common feature of the sensory and motor cortices. Similar to their excitatory counterparts, subsets of Somatostatin- and Parvalbumin-expressing neurons have been shown to innervate distal targets like the sensory and motor striatum and the contralateral cortex. However, no evidence of long-range VIP neurons, the third major class of GABAergic cortical inhibitory neurons, has been shown in such cortical regions. Here, using anatomical anterograde and retrograde viral tracing, we tested the hypothesis that VIP-expressing neurons of the mouse auditory and motor cortices can also send long-range projections to cortical and subcortical areas. We were able to demonstrate, for the first time, that VIP-expressing neurons of the auditory cortex can reach not only the contralateral auditory cortex and the ipsilateral striatum and amygdala, as shown for Somatostatin- and Parvalbumin-expressing expressing long-range neurons, but also the medial geniculate body and both superior and inferior colliculus. We also demonstrate that VIP-expressing neurons of the motor cortex send long-range GABAergic projections to the dorsal striatum and contralateral cortex. Because of its presence in two such disparate cortical areas, this would suggest that the long-range VIP projection is likely a general feature of the cortex's network.